2006
DOI: 10.1074/jbc.m607168200
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Factor Interactions and Somatic Silencing of the Germ Cell-specific ALF Gene

Abstract: Germ cell-specific genes are active in oocytes and spermatocytes but are silent in all other cell types. To understand the basis for this seemingly simple pattern of regulation, we characterized factors that recognize the promoter-proximal region of the germ cell-specific TFIIA␣/␤-like factor (ALF) gene. Two of the protein-DNA complexes formed with liver extracts (C4 and C5) are due to the zinc finger proteins Sp1 and Sp3, respectively, whereas another complex (C6) is due to the transcription factor RFX1. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…Since the amino and carboxy termini of BORIS have no homology with the parallel sequences in CTCF, the distinct molecular functions of BORIS may be attributable to the unique protein-protein interactions specified by these sequences. Our observations on the role of BORIS binding site in activation of the CST form F TS transcription are remarkably consistent with results on regulation of testis-specific TFIIA ␣/␤-like factor (ALF) gene promoter obtained by DeJong and coworkers, who showed that unlike CTCF, expression of BORIS had an activating effect on the ALF promoter-reporter construct (9,26). However, ALF only starts to express at the time point we performed microarray analysis, and that may be why we missed it as a target (15).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the amino and carboxy termini of BORIS have no homology with the parallel sequences in CTCF, the distinct molecular functions of BORIS may be attributable to the unique protein-protein interactions specified by these sequences. Our observations on the role of BORIS binding site in activation of the CST form F TS transcription are remarkably consistent with results on regulation of testis-specific TFIIA ␣/␤-like factor (ALF) gene promoter obtained by DeJong and coworkers, who showed that unlike CTCF, expression of BORIS had an activating effect on the ALF promoter-reporter construct (9,26). However, ALF only starts to express at the time point we performed microarray analysis, and that may be why we missed it as a target (15).…”
Section: Discussionsupporting
confidence: 92%
“…Methylation interference assays followed by EMSA with mutated fragments revealed that the exact BORIS binding site in the promoter is highly homologous to the TAGGGGG-containing CTCF/BORIS binding sequence mapped by DeJong and coworkers in the testis-specific ALF gene promoter (8,26), which has been termed the consensus CTCF binding site as identified by genome-wide ChIP analysis (27). Consistent with the finding of a BORIS/CTCF target site in the promoter, ectopic expression of BORIS activated the CST form F TS promoter, but not the promoter mutated in the BORIS/CTCF target site.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies established a correlation between the methylation status of the promoter and gene expression for some testis-specific genes (42). A recent study implicated CTCF and Sp3 in mediating somatic repression of a testis-specific gene (43). Our study shows how an insulator located in a CpG-free proximal promoter can regulate testis-specific gene transcription.…”
Section: Discussionsupporting
confidence: 58%
“…The importance of such experimental validation is reinforced by the recent discovery of several functional CTSs that do not match any in-silico-generated CTSs consensus motif. Examples include CTSs in the hTERT (44) and ALF (45) gene promoters, and numerous methylation-sensitive and methylation-resistant CTSs in the promoter regions of the human BORIS gene (46) and in pericentromeric gamma-satellite DNA arrays. (18) Finally, the data on CTSs provided by genome-wide screening have limitations as although these studies present indications of the binding position, they only give approximations of the length of the region of DNA bound by CTCF.…”
Section: Ctcf-dna Interactionsmentioning
confidence: 99%